FUNCTIONS OF ATOMS RADIAL DISTRIBUTION AND PAIR POTENTIAL OF SOME SEMICONDUCTORS MELTS - А. Z. Issagulov; D. Belomestny; G. S. Shaiкhova; V. V. Zhurov; L. Zh. Kasymova; G. Zh. Zhetimekova (Scientific Journal of Pedagogy and Economics, 2019)
The paper presents an estimate of the pair potential and the construction of the curves of the radial distribution of atoms in some melts of semiconductors such as germanium, silicon using the conducted studies in the framework of the density functional. The results of calculations of the potential for pair interaction in a germanium melt with the use of experimental data by V. M. Glazov and quantum potentials of pair interaction obtained by quantum chemical methods, respectively. The temperature dependences of the radial distribution function of atoms in melts of selenium, tellurium, silicon, and germanium are studied theoretically. The results of the calculation of the radial distribution of atoms calculated by the molecular dynamics method are considered. If we assume that the position of the first maximum of the radial distribution curve of atoms in the melt corresponds to the shortest interatomic distance in atomic chains, then we must conclude that during the melting of a crystal this distance increases and a distorted crystal structure is obtained. The potential of pair interplay in melts of germanium, silicon with usage of the conducted researches is estimated within the framework of a functional of density. The pair potentials are calculated under the electrostatic theorem of Gelman-Feynman, after finding of optimum electronic density conforming to equilibrium internuclear spacing interval.